Безсистемність антикорупційної суб’єктності патронатних службовців: «громадські засади» та інші квазіновації - Хамходера, Олег Петрович; Хамходера, О. П.; Хамходера, Олег Петрович; Khamkhodera, Oleh P. (My University, 2020)
Статтю присвячено теоретичним і позитивно-правовим основам зарахування патронатних службовців до кола осіб, на яких поширюється дія антикорупційного законодавства. Охарактеризовано проблеми запровадження критерію «громадські засади» як підстави нівелювання антикорупційної суб’єктності, безсистемність утвердження останньої стосовно сервісних агентів. З’ясовано, що муніципальні патронатні функціонери зазнають і зазнавали антикорупційного регулювання.

The article is devoted to the theoretical and positive legal bases of inclusion of patronage employees in the circle of persons covered by the anti-corruption legislation. The problematic aspects of the introduction of the criterion of “public principles” as a basis for leveling the anti-corruption subjectivity are singled out and characterized: its contextual insignificance (lack of significance for the purposes of thematic regulation); the property of gratis volunteer service conditions for many functionaries and quasi-functionaries directly enshrined in the thematic subjectivity of functionaries and quasi-functionaries; the likelihood (albeit ideological unfoundedness) of manipulative references to the public nature of the service in some jurisdictional proceedings. The incoherence and selectivity of the legislative qualification of patronage officials as persons covered by the Law “On the Prevention of Corruption” are criticized, in particular: a) the period of privileged position of parliamentary “patrons”, which had no substantive motivation, is predictably had over, left unnecessary (meaningless, dead) wording-exceptions in a number of regulations; b) The period of burdened position of presidential and court patronage officials (in context of general loyalty to other service agents), which is also not meaningfully harmonious. The integrity of the coverage by the sectoral legislation of public quasi-functionaries (in competitive or disciplinary commissions) was positively assessed. The absence of anti- corruption subjectivity entity of the judge assistants of the CCU has been proved, validity and longevity of which has been questioned. It has been established that municipal patronage officials: face and had faced anticorruption regulation (within the concept of “local government officials”), categorially separated from other “patrons”, actualize the more general problematique of systematic of public service.

Статья посвящена теоретическим и позитивно-правовым основам зачисления патронатных служащих к кругу лиц, на которых распространяется действие антикоррупционного законодательства. Охарактеризованы проблемы внедрения критерия «общественные начала» как основания нивелирования антикоррупционной субъектности, бессистемность утверждения последней для сервисных агентов. Выяснено, что муниципальные патронатные функционеры подвергались и подвергаются антикоррупционному регулированию.
Хамходера О. П. Безсистемність антикорупційної суб'єктності патронатних службовців: «громадські засади» та інші квазіновації / О. П. Хамходера // Журнал східноєвропейського права. – 2020. – Вип. 77. – С. – 152-162.
Keywords: декларування; запобігання корупції; конфлікт інтересів; помічник судді; публічна служба; сумісництво; суміщення; declaration; prevention of corruption; conflict of interest; assistant judge; public service; combination; декларирование.; предотвращения коррупции; конфликт интересов; помощник судьи; публичная служба; совместительство; Research Subject Categories::LAW/JURISPRUDENCE; secondary jobs